Cognitive and Physiological Measures in Well-Being Science: Limitations and Lessons - Yetton, Benjamin D.; Revord, Julia; Margolis, Seth; Lyubomirsky, Sonja; Seitz, Aaron R. (Frontiers in Psychology, 2019)
Social and personality psychology have been criticized for overreliance on potentially biased self-report variables. In well-being science, researchers have called for more “objective” physiological and cognitive measures to evaluate the efficacy of well-being-increasing interventions. This may now be possible with the recent rise of cost-effective, commercially-available wireless physiological recording devices and smartphone-based cognitive testing. We sought to determine whether cognitive and physiological measures, coupled with machine learning methods, could quantify the effects of positive interventions. The current 2-part study used a college sample (N = 245) to contrast the cognitive (memory, attention, construal) and physiological (autonomic, electroencephalogram) effects of engaging in one of two randomly assigned writing activities (i.e., prosocial or “antisocial”). In the prosocial condition, participants described an interaction when they acted in a kind way, then described an interaction when they received kindness. In the “antisocial” condition, participants wrote instead about an interaction when they acted in an unkind way and received unkindness, respectively. Our study replicated previous research on the beneficial effects of recalling prosocial experiences as assessed by self-report. However, we did not detect an effect of the positive or negative activity intervention on either cognitive or physiological measures. More research is needed to investigate under what conditions cognitive and physiological measures may be applicable, but our findings lead us to conclude that they should not be unilaterally favored over the traditional self-report approach.